Food safety knowledge, attitudes and practices among the street food vendors in Gaya Street, Sabah - Saidul, Nurul Fazilah Azuana (2018)
This study is to investigated the knowledge, attitude and practices on food safety among the street food vendors in Gaya Street, Sabah. Using quantitative approach, self-administered questionnaire was distributed to 77 street food vendors. Although food handler may be aware about the need for personal hygiene and food hygiene, they do not understand about the food hygiene such the time to cook of foods. All the completed questionnaires were checked manually and data were analysis by computer using SPSS version 22.0 software package. Chi-square analysis that age, educational level, business experience and training on food safety appeared no association towards food safety (p>0.05). , where personal hygiene knowledge and contamination appeared has association towards food safety practice (p<0.05) and self-improvement and responsibility also appeared have association towards food safety practices (p<0.05). Thus null hypothesis is rejected. Finding of this study may help in to improve the knowledge, attitude and practices towards food-borne disease and food safety that ensure the foods are safe to be consume by consumers.